A Comparative Study on Bushmeat Consumption Patterns in ten Tribes in Tanzania. (June 2014) - Ceppi, Silvia Laura; Nielsen, Martin Reinhardt
Bushmeat hunting is an important driver of wildlife depletion in Tanzania, but national-wide estimates of its consumption are lacking. We compare bushmeat consumption frequencies and determinants in ten tribes in different ecoregions in Tanzania, four of these within biodiversity hotspots of global conservation importance. Bushmeat consumption is examined in terms of ethnicity, selected indicators of wealth, and distance to and protection level of nearest protected area. Forty six percent of the respondents (n=300) belonging to nine of the ten tribes reported consuming bushmeat during the past 12 months, and 14% admitted that at least one household member hunted illegally. Significant differences in bushmeat consumption frequencies and species consumed were observed among ethnic groups. Regression revealed that the presence of a hunter in the household increased significantly the prevalence of bushmeat consumption, while distance to and protection level of nearest protected area had the most significant negative effect. Anti-poaching patrols are an effective deterrent to illegal bushmeat consumption, whilst access to domestic animal protein and other selected indicators of wealth do not reduce bushmeat consumption. The results emphasise the importance of strengthening anti-poaching services and the integration of cultural differences in preference for bushmeat into policies aimed at reducing bushmeat consumption and conserving wildlife.